2023
DOI: 10.1021/jacs.3c01644
|View full text |Cite
|
Sign up to set email alerts
|

Infinitenes as the Most Stable Form of Cycloarenes: The Interplay among π Delocalization, Strain, and π–π Stacking

Abstract: The recent successful preparation of infinitene has sparked widespread attention due to its aesthetic appeal and synthetic challenge. Spectroscopic measurements and follow-up computational investigations suggest that infinitene holds fundamental significance and potential applications in chiroptics, optoelectronics, asymmetric synthesis, and supramolecular chemistry. However, unlike other looped polyarenes enriched with sizes and shapes, the infinitene molecule seems, so far, the only known example of this fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 113 publications
5
23
0
Order By: Relevance
“…If a segment of a CNB comprises more than six rings in a row, the HOMO−LUMO gap is expected to be so narrow that the electronic ground state is most likely an open-shell singlet with a polyradical character. A similar phenomenon has been found in the case of linear oligoacenes, 66 generalized infinitenes, 20 and generalized kekulenes. 21 The extreme case is the zigzag CNBs (n, 0), or the so-called [n]cyclacenes.…”
Section: Homo−lumo Gaps Of Standard Cnbssupporting
confidence: 79%
See 2 more Smart Citations
“…If a segment of a CNB comprises more than six rings in a row, the HOMO−LUMO gap is expected to be so narrow that the electronic ground state is most likely an open-shell singlet with a polyradical character. A similar phenomenon has been found in the case of linear oligoacenes, 66 generalized infinitenes, 20 and generalized kekulenes. 21 The extreme case is the zigzag CNBs (n, 0), or the so-called [n]cyclacenes.…”
Section: Homo−lumo Gaps Of Standard Cnbssupporting
confidence: 79%
“…4,8 As a more strict definition, CNBs are considered by many chemists as double-stranded structures with a single layer of benzene rings, 3,5,7,9−15 although multilayered nanobelts, such as the Vogtle belt, 16,17 are also frequently known. 13,18,19 Due to their cylindrical carbon skeleton, CNBs are highly strained molecules, and first-principles calculations 20,21 have shown that they are generally higher in energy than the macrocyclic topoisomers of other types, like the generalized kekulenes, 20−22 clarenes, 20,21 and even the doubly twisted infinitene 23 and its generalized analogues. 20,24,25 become a long-standing synthetic target for ambitious chemists since the first CNB molecule, [n]cyclacene, was theoretically conceived in 1954.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystal structure analysis has shown that the combined lamellar and herringbone-like packing structure introduced three-dimensional electronic interactions caused by the infinity shape. Since this report, fascinating properties of infinitene have been predicted. Wu and Isobe et al synthesized a twisted CNB in 2021 and a fused [5]­helicene dimer in 2023 , as a related molecule of infinitene. In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported. In 2019, Tanaka et al synthesized the first oxygen-embedded CNB by rhodium-catalyzed alkyne cyclotrimerization .…”
Section: Synthesis Of Cnbs and Related Aromatic Beltsmentioning
confidence: 98%
“…As one example, the long-held general practice in assigning UV–vis spectra obtained with dissolved molecular chromophore as an absorbance spectrum is generally invalid for solutions containing nanoscale or larger materials. This is because both absorption and scattering contribute to the UV–vis extinction spectra. Further complication arises if one considers interference of forward scattered and emitted photons in the UV–vis spectral acquisition. However, it has been prevalent in current literature to assign the UV–vis spectrum as absorbance or absorption extinction spectrum, even for samples likely having strong scattering activities. The impact on the scattering activity of numerous nanomaterials has been published extensively in previous works. , …”
Section: Introductionmentioning
confidence: 99%